2022
DOI: 10.3390/antiox11102029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Copper Exposure on Oxidative Stress, Apoptosis, Endoplasmic Reticulum Stress, Autophagy and Immune Response in Different Tissues of Chinese Mitten Crab (Eriocheir sinensis)

Abstract: High concentrations of copper (Cu2+) pose a great threat to aquatic animals. However, the mechanisms underlying the response of crustaceans to Cu2+ exposure have not been well studied. Therefore, we investigated the alterations of physiological and molecular parameters in Chinese mitten crab (Eriocheir sinensis) after Cu2+ exposure. The crabs were exposed to 0 (control), 0.04, 0.18, and 0.70 mg/L of Cu2+ for 5 days, and the hemolymph, hepatopancreas, gills, and muscle were sampled. The results showed that Cu2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…Moreover, they attributed this reduction in antioxidant enzyme activities to the copper-induced escalation in the production of reactive oxygen species (ROS). Another study conducted by Feng et al (2022) explored changes in physiological and molecular parameters in Chinese mitten crabs following exposure to copper. This investigation revealed that copper exposure led to oxidative stress, apoptosis, endoplasmic reticulum stress, autophagy, and an immune response in various tissues of Chinese mitten crabs.…”
Section: Effect Of Fenvalerate On Antioxidant Enzyme Activities and M...mentioning
confidence: 99%
“…Moreover, they attributed this reduction in antioxidant enzyme activities to the copper-induced escalation in the production of reactive oxygen species (ROS). Another study conducted by Feng et al (2022) explored changes in physiological and molecular parameters in Chinese mitten crabs following exposure to copper. This investigation revealed that copper exposure led to oxidative stress, apoptosis, endoplasmic reticulum stress, autophagy, and an immune response in various tissues of Chinese mitten crabs.…”
Section: Effect Of Fenvalerate On Antioxidant Enzyme Activities and M...mentioning
confidence: 99%
“…Copper is an important nutrient involved in a variety of biological functions including mitochondrial respiration, oxidative stress, and cytotoxicity. [19][20][21] Dysregulation of copper homeostasis has been associated with tumor proliferation, angiogenesis, and metastasis, suggesting that copper may play a role in tumor progression. [22][23][24] Studies have found that liver copper content is closely related to HCC, and serum copper and ceruloplasmin levels could be used as markers for HCC detection.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, neonicotinoid insecticide exposure can alter the activity of drug-metabolizing enzymes in the hepatopancreas (the major organ of drug metabolism) of Eriocheir sinensis , most commonly cytochrome P450, which acts as a class of the subtilisin family of proteins involved in phase I detoxification processes [ 28 ]. Cytochrome P450 is also considered to be an important and sensitive parameter for the detection of environmental toxicants [ 29 ]. After the first phase of detoxification, glutathione-S-transferase (GST) begins to participate in the second phase of detoxification by catalyzing the coupling reaction between glutathione (GSH) and toxic substances, which increases the water solubility of toxic compounds and thus facilitates their excretion from the body, ultimately achieving the detoxification effect [ 30 ].…”
Section: Introductionmentioning
confidence: 99%